Promotion of Immunizations for Health Professionals in Europe: A Qualitative Study in Seven European Member States - Dalma, Archontoula; Karnaki, Pania; Baka, Agoritsa; Raftopoulos, Vasilios; Zota, Dina; Veloudaki, Afroditi; Garrison, Amanda; Ellis Montalban, Paloma; Dhanani, Zainub; Linos, Athena (My University, 2018)
Health Care Workers (HCWs) are a high-risk group for contracting Vaccine-Preventable Diseases who, despite legislation and guidance, remain undervaccinated. In order to understand their barriers and needs, focus groups were formed with 278 physicians, nurses, infection-control personnel, and policy-makers in 7 EU MS. Several implications for the development of promotional initiatives were identified including the need to overcome organizational barriers, to sensitize HCWs about the importance of immunization and to provide specific up-to-date information about vaccinations covering prevalence of diseases, protection years, side effects, administration times, antibody examinations, costs and immunization settings.
Keywords: Barriers; Europe; Focus groups; Healthcare workers; Immunization